Experimental validation and computational modeling of anti-influenza effects of quercetin-3-O-α-L-rhamnopyranoside from indigenous south African medicinal plant Rapanea melanophloeos - Parvaneh Mehrbod; Samad Nejad Ebrahimi; Fatemeh Fotouhi; Fatemeh Eskandari; Jacobus N. Eloff; Lyndy J. McGaw; Folorunso O. Fasina (BMC, 2019)
Abstract Background Influenza A virus (IAV) is still a major health threat. The clinical manifestations of this infection are related to immune dysregulation, which causes morbidity and mortality. The usage of traditional medication with immunomodulatory properties against influenza infection has been increased recently. Our previous study showed antiviral activity of quercetin-3-O-α-L-rhamnopyranoside (Q3R) isolated from Rapanea melanophloeos (RM) (L.) Mez (family Myrsinaceae) against H1N1 (A/PR/8/34) infection. This study aimed to confirm the wider range of immunomodulatory effect of Q3R on selective pro- and anti-inflammatory cytokines against IAV in vitro, to evaluate the effect of Q3R on apoptosis pathway in combination with H1N1, also to assess the physical interaction of Q3R with virus glycoproteins and RhoA protein using computational docking. Methods MDCK cells were exposed to Q3R and 100CCID50/100 μl of H1N1 in combined treatments (co-, pre- and post-penetration treatments). The treatments were tested for the cytokines evaluation at RNA and protein levels by qPCR and ELISA, respectively. In another set of treatment, apoptosis was examined by detecting RhoA GTPase protein and caspase-3 activity. Molecular docking was used as a tool for evaluation of the potential anti-influenza activity of Q3R. Results The expressions of cytokines in both genome and protein levels were significantly affected by Q3R treatment. It was shown that Q3R was much more effective against influenza when it was applied in co-penetration treatment. Q3R in combination with H1N1 increased caspase-3 activity while decreasing RhoA activation. The molecular docking results showed strong binding ability of Q3R with M2 transmembrane, Neuraminidase of 2009 pandemic H1N1, N1 and H1 of PR/8/1934 and Human RhoA proteins, with docking energy of − 10.81, − 10.47, − 9.52, − 9.24 and − 8.78 Kcal/mol, respectively. Conclusions Quercetin-3-O-α-L-rhamnopyranoside from RM was significantly effective against influenza infection by immunomodulatory properties, affecting the apoptosis pathway and binding ability to viral receptors M2 transmembrane and Neuraminidase of 2009 pandemic H1N1 and human RhoA cellular protein. Further research will focus on detecting the detailed specific mechanism of Q3R in virus-host interactions.